A Snapshot of Doctoral Training in Epidemiology: Positioning Us for the Future. Issue 10 (8th May 2020) - Hlaing, WayWay M; Schmidt, Renae D; Ahn, Soyeon; Samet, Jonathan M; Brownson, Ross C
Abstract: Although epidemiology core competencies are established by the Association of Schools and Programs of Public Health for masters-level trainees, no equivalent currently exists for the doctoral level. Thus, the objective of the Doctoral Education in Epidemiology Survey (2019) was to collect information on doctoral-level competencies in general epidemiology (doctoral) degree programs and other pertinent information from accredited programs in the United States and Canada. Participants (doctoral program directors or knowledgeable representatives of the program) from 57 institutions were invited to respond to a 39-item survey (18 core competencies; 9 noncore or emerging topic–related competencies; and 12 program-related items). Participants from 55 institutions (96.5%) responded to the survey, of whom over 85% rated 11 out of 18 core competencies as "very important" or "extremely important." More than 80% of the programs currently emphasize 2 of 9 noncore competencies (i.e., competency to ( 1 ) develop and write grant proposals, and ( 2 ) assess evidence for causality on the basis of different causal inference concepts). "Big data" is the most frequently cited topic currently lacking in doctoral curricula. Information gleaned from previous efforts and this survey should prompt a dialog among relevant stakeholders to establish a cohesive set of core competencies for doctoral training in epidemiology.